The Effect of GeoGebra Software in Calculus for Mathematics Teacher Students - Prapaporn Nongharnpituk,; Wannatida Yonwilad,; Paweena Khansila, (Journal of Educational Issues, 2024)
The objectives of these mixed methods were to 1) improve students’ performance in calculus by using GeoGebra software and 2) investigate students’ experiences with and perspectives on using GeoGebra software in calculus. The participants were 58 mathematics teacher students at a university in Thailand. The instruments in this study were a test; this was called the Calculus Achievement Test (CAT), which consists of limits and continuity; a derivative of function; and its application; and a questionnaire with an interview with a student. The statistics for qualitative data were gathered from instruction; we used percentages, mean scores, standard deviations, and a one-sample t-test; while quantitative data was gathered from students’ reflections and interviews. The results showed: 1) the results of the one-sample t-test show that using GeoGebra Software in Calculus is effective in students’ performance; 2) the data, the quantitative findings show that students were more interested and excited during the intervention. Students could better show their creativity and learn about themselves because of the intervention. Teaching calculus with GeoGebra embedded is a good and effective way to do things. The finding shows a good chance of developing technology-integrated math curricula for teaching and learning calculus.